2016
DOI: 10.1038/pr.2016.138
|View full text |Cite
|
Sign up to set email alerts
|

Is urinary neutrophil gelatinase-associated lipocalin able to predict acute kidney injury episodes in very low birth weight infants in clinical settings?

Abstract: Although UNGAL elevation > 50 ng/ml discriminates between pre-AKI and non-AKI days, high false positive and false negative rates limit utility as a screening test in VLBW newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Figure 2 shows a plot of log(uNGAL) vs. the time interval of post-operative urine collection in hours. Individual uNGAL trajectories by subject, shown in light gray, demonstrate wide uNGAL variability even at baseline, where one-third of uNGAL values exceeded 50 ng/mL, the predictive cut off for AKI noted for older children and very low birthweight infants [14,[18][19][20][21] (Table 1, Figure 2). Mean trajectories for those with and without AKI are derived from a single, mixed-effects hierarchical model regressing log(uNGAL) on the interaction of time interval and AKI status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows a plot of log(uNGAL) vs. the time interval of post-operative urine collection in hours. Individual uNGAL trajectories by subject, shown in light gray, demonstrate wide uNGAL variability even at baseline, where one-third of uNGAL values exceeded 50 ng/mL, the predictive cut off for AKI noted for older children and very low birthweight infants [14,[18][19][20][21] (Table 1, Figure 2). Mean trajectories for those with and without AKI are derived from a single, mixed-effects hierarchical model regressing log(uNGAL) on the interaction of time interval and AKI status.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous analysis exploring the relationship between uNGAL values and AKI in very low birthweight infants demonstrated that uNGAL >50 ng/mL had a sensitivity of 66% and a specificity of 66% to predict AKI [14]. Using this data in combination with our institutional prevalence rate of 25% for post-operative AKI in neonates undergoing cardiac surgery with CPB, we performed a power analysis to determine the number of neonates required to discriminate sensitivity and 1-specificity.…”
Section: Power Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Otros pacientes iniciarán con hipertensión arterial. 1,5 Un indicador de IRA es la elevación de la creatinina sérica; sin embargo, en las primeras 72 horas de vida ésta podría reflejar los niveles maternos. 4 Además, los niveles se modifican por el sexo, la masa muscular, el metabolismo, el uso de drogas y otros componentes endógenos.…”
Section: Wwwmedigraphicorgmx Introducciónunclassified